A Review of Mechanical Properties on the Potential Use of Reclaimed Asphalt Pavement (RAP) as Aggregate Substitute in Concrete Mixtures - Azman, Muhammad Ikhwan Nurzaman; Ahmad Jeni, Mohamad Luthfi (Progress in Engineering Application and Technology, 2021)
The use of industrial and infrastructural waste has gained considerable significance in civil engineering applications. The result of removing old material from the asphalt pavement is the Reclaimed Asphalt Pavement (RAP). RAP consists of a well-graded, asphalt-cement-coated aggregate of high quality. RAP in concrete mixing formulation is a system that is part of a strategy for sustainable production as it eliminates the use of new aggregates and reuses a resource considered waste. This paper will determine the best potential of using RAP waste as a substitute to aggregate, neither on fine or coarse aggregate. The use of RAP in concrete as an aggregate substitute is increasingly driven by potential challenges relating to the loss of good aggregate supplies and the maintenance of stocks of surplus RAP. In contrast to the control concrete mixture, the RAP concrete mixtures exhibited improved ductility and high strain power. Earlier experiments showed the viability of making concrete with RAP aggregate; previous studies, however, focused on the material’s mechanical properties. An appropriate test for field modulus prediction and general effects of such features was also found in previous studies on these waste materials’ behaviours. Based on this dissertation’s findings, this paper presents more detrimental results than replacing both fine and coarse or either the rough quantity of aggregates by replacing only the substantial portion of aggregates with their corresponding RAP.